ANALISIS PENINGKATAN KESEJAHTERAAN EKONOMI MASYARAKAT PESISIR WISATA PANTAI DUTA - Jazuli (Lembaga Penerbitan, Penelitian, dan Pengabdian kepada Masyarakat (LP3M) of Institut Badri Mashduqi Probolinggo Jawa timur Indonesia, 2023)
The main problem in this study is the increase in the economic welfare of the randu tata community with duta beach tourism. Since the presence of duta beach tourism. Researchers are interested in researching this problem because it is felt that there is a need for an in-depth study of the economic welfare of the people around randu tata after the duta beach tour. The method used in this research is a qualitative method using a phenomenological approach. The technique used in collecting data is by direct field observation and careful research on the research object. The data analysis technique used is descriptive qualitative analysis, the data processing process goes through three stages namely data reduction, data presentation and verification or drawing conclusions. Improving little by little. And the surrounding community is very happy with duta beach tourism, because their income is increasing.